Primary squamous cell carcinoma of the parotid salivary gland: a clinical observation - N. A. Ognerubov; A. O. Khizhnyak; М. A. Ognerubova; R. S. Sergeev; L. V. Polyakova (Опухоли головы и шеи)
Introduction. Malignant tumors of the salivary glands account for 3–5 % of all cases of head and neck cancer. Squamous cell carcinoma is the rarest histological variant of this pathology. It accounts for an average of 1.6 %. Among large salivary gland tumors, squamous cell carcinoma most often occurs in the parotid salivary gland.Aim. To present a clinical case of primary disseminated cancer of the parotid salivary gland with squamous cell structure.Clinical observation. A 70-year-old patient was under observation who was diagnosed with a primary squamous cell tumor of the parotid salivary gland with multiple metastases during a complex examination. He was sick for about 6 months when asymmetry of left half of the face appeared due to a painful neoplasm in the parotid salivary gland. Recently, the patient has noted increased tumor growth. Objective examination revealed peripheral paralysis of the facial nerve on the left. In the parotid-masticatory region on the left, with a transition to the zygomatic region, there is a dense painful immobile exophytic tumor with infiltration into soft tissues of the face and skin 6.5 × 5.0 cm in size with an ulcer in the center. Laterally, it reaches the tragus, and at the bottom-the angle of the lower jaw. In the submandibular region on the left, metastatic lymph nodes 2.5 × 2.0 cm in size are palpated. A biopsy was collected. Histological conclusion: non-keratinizing squamous cell carcinoma. Expression of the programmed death receptor ligand (PD-L1) in the tumor is negative. Mutations of genes Her2-neu and BRAF were not detected. According to medical imaging methods, multiple metastases were found in the lungs, liver, zygomatic bone and tumor growth in the maxillary sinus on the left. The diagnosis was established: cancer of the parotid salivary gland, stage IVC, cT4N1M1, with metastases to the liver, lungs and bones. Polychemotherapy was prescribed according to the scheme: 5-fluorouracil + cisplatin + cetuximab + bisphosphonates. After 3 cycles, a partial regression is obtained.Conclusion. The primary squamous cell carcinoma is prone to an aggressive course and has an unfavorable prognosis, especially in patients over 60 years of age with skin and facial nerve damage, as well as the presence of regional and distant metastases. Differential diagnosis is necessary to exclude the secondary nature of the tumor. The presented case is a rare example of primary squamous cell carcinoma of the parotid salivary gland with extensive metastatic lesion and regression of the pathological process after polychemotherapy in combination with targeted therapy.